1970
DOI: 10.3329/uhj.v5i2.4558
|View full text |Cite
|
Sign up to set email alerts
|

Subxiphoid window drainage of pericardial effusion - study of 35 cases

Abstract: Pericardial effusion defines the presence of an abnormal amount and/or character of fluid in the pericardial space. It can be acute or chronic and caused by a variety of local and systemic disorders, or it may be idiopathic. Pericardial effusion can be relieved by medical treatment, pericardiocentesis through a needle with or without echocardiographic guidance, or by surgical procedures, such as subxiphoid pericardial tube drainage, by creating a pericardial window through a left anterior thoracotomy, or by vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Our finding is in keeping with findings of Agner and Gallis, who observed that tuberculosis and malignant effusion were more likely to cause large pericardial effusion, effusion causing haemodynamic compromise compared to those secondary to idiopathic pericarditis [ 11 ]. Other studies done in regions with high endemicity for TB also revealed TB as the most common cause of pericardial effusion [ 12 , 13 ]. All our patients suspected to have TB pericardial effusion received an initial 4-drug therapy for 2 months (isoniazid, rifampicin, pyrazinamide, and ethambutol) followed by isoniazid and rifampicin for the remaining 4 months.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our finding is in keeping with findings of Agner and Gallis, who observed that tuberculosis and malignant effusion were more likely to cause large pericardial effusion, effusion causing haemodynamic compromise compared to those secondary to idiopathic pericarditis [ 11 ]. Other studies done in regions with high endemicity for TB also revealed TB as the most common cause of pericardial effusion [ 12 , 13 ]. All our patients suspected to have TB pericardial effusion received an initial 4-drug therapy for 2 months (isoniazid, rifampicin, pyrazinamide, and ethambutol) followed by isoniazid and rifampicin for the remaining 4 months.…”
Section: Discussionmentioning
confidence: 94%
“…Orthopnea was particularly observed in patients who presented with cardiac tamponade. Other studies have reported dyspnoea as the most common symptoms [ 11 , 12 ]. Many patients (43.8%) presented with history and echocardiographic features in keeping with cardiac tamponade because generally in the developing world most of our patients present late.…”
Section: Discussionmentioning
confidence: 99%